The Impact of Word of Mouth, Store Atmosphere, Service Quality and Customer Satisfaction on Purchase Decisions in Global Store South Labuhanbatu District Mobile Phone - Mulia, Budi; Nasution, Meisa Fitri; Halim, Abd (Journal of Applied Business Administration, 2024)
The purpose of this study is to examine how customer satisfaction, service quality, word-of-mouth, and store atmosphere affect consumers' decisions to buy at the Global Cell Phone Store in South Labuhanbatu Regency. The research employed observation, documentation, and Likert scale questionnaires as data gathering methods. Customers of the Global Mobile Shop in South Labuhanbatu Regency made up the study's population. There were 110 customer samples in all in this study. Multiple linear regression, assessed using partial (t), simultaneous (F), and coefficient of determination tests, is the analytical tool employed in this study. At the Global Mobile Shop in South Labuhanbatu Regency, partial and concurrent research results demonstrate that customer contentment, shop atmosphere, word-of-mouth, and service quality have a favorable and significant impact on purchase decisions.